صناديق الزكاة نموذج للتنمية المستدامة دراسة حالة صندوق الزكاة لولاية بسكرة- الفترة: (2003-2013) - بن الزاوي, إشراق (جامعة الوادي - University of Eloued, 2017)
تعتبر الزكاة مورد اقتصادي هام يجب العمل به في تنظيم الموارد المالية وطرق إنفاقها، وتتميز الزكاة بأنها أحد الإيرادات العامة للدولة ومن خصائصها اتساع ونمو حصيلتها وتنوع وعائها، وتعتبر الدولة هي المسؤولة عن الزكاة جباية وصرفا، فقد كان في السابق هذا الأمر متروكا للمواطنين أنفسهم بسبب التوزيع الفردي للزكاة، وهو ما دفع إلى إنشاء صناديق للزكاة، ومع إنشاء هذه الصناديق في الدول الإسلامية التي أصبحت أداة فعالة في عملية التنمية من خلال الدور الكبير الذي تؤديه في إعادة توزيع الثروة والدخل ومحاربة الاكتناز وتشجيع الاستثمار والتخفيف من مشاكل البطالة وذلك من خلال دعم استثمار أموال الزكاة في مختلف أنواع المشاريع التي تساهم في التنمية، حيث أن منح صندوق الزكاة للأموال من أجل الاستثمار له دور كبير في تحقيق أبعاد التنمية المستدامة، فقد اكتسبت التنمية المستدامة أهمية كبيرة على الصعيد العالمي، خصوصاً مع انعقاد قمة البيئة والتنمية في البرازيل عام 1992، والتي نتج عنها جدول أعمال القرن الحادي والعشرين، والذي يشكل خطة عالمية لتحقيق التنمية المستدامة وتأسيس لجنة الأمم المتحدة للتنمية المستدامة. ولإبراز الدور الذي تؤديه صناديق الزكاة في تحقيق مختلف أبعاد التنمية المستدامة تمت دراسة حالة صندوق الزكاة لولاية بسكرة وذلك بالوقوف على أهم المشاريع التي تم تمويلها من طرف الصندوق عن طريق القرض الحسن والتي لها أثرها الاقتصادي والاجتماعي والبيئي. إن حصيلة الزكاة والمشاريع الممولة من طرف صندوق الزكاة لولاية بسكرة تعتمد على البعد الاجتماعي كهدف أساسي في التنمية، يليه البعد البيئي والتكنولوجي، ولم يتم اعتماد البعد الاقتصادي كهدف أساسي في التنمية المستدامة، وعليه لابد من قيام صندوق الزكاة بالموازنة بين أهدافه لأن كل بعد يرتبط بالأبعاد الأخرى. Zakat is an important economic resource that must be used in the organization of financial resources and ways of spending it. It is characterized as one of the public revenues of the state, and some of its characteristics are the breadth and growth of its revenues and the diversity of its receptacle. The state is responsible for the collection and the disbursement of Zakat. In the past, this process was up to the citizens themselves because of the individual distribution of Zakat, which led to the establishment of zakat funds. Having founded this in the Islamic countries, which has become an effective tool in the development process through the major role played in the redistribution of wealth and income, fighting the compactness and encouraging investment, and alleviating the problems of unemployment, the Zakat fund Investment has had a significant role in achieving the dimensions of sustainable development. Sustainable development has gained great importance globally, especially with the convening of the Environment and Development Summit in Brazil in 1992 that had resulted in the Agenda of the 21st century, which constitutes a global plan for sustainable development and the establishment of the United Nations Commission on Sustainable Development. In order to highlight the role played by the Zakat Funds in achieving the various dimensions of sustainable development, the Zakat Fund has been studied in the Province of Biskra by standing upon the projects that was financed by the Fund through benevolent loan, which has an economic, social and environmental impact. The Zakat Fund and the projects it finances for the State of Biskra depend on the social dimension as a main objective in development, followed by the environmental and technological dimension. The economic dimension is not adopted as a primary goal in sustainable development. Therefore, the Zakat Fund must balance its objectives because all dimensions are interrelated.
Zakat Funds: A model for Sustainable Development Case Study of Zakat Funds for the Province of Biskra - Period: (2003-2013)
Keywords: لزكاة، صندوق الزكاة، القرض الحسن، التمويل، التنمية المستدامة; Zakat, Zakat Fund, benevolent loan, Finance, Sustainable Development.